Adaptive control of electrically‐driven nonholonomic wheeled mobile robots: Taylor series‐based approach with guaranteed asymptotic stability. (26th February 2020) - Haqshenas M., AmirReza; Fateh, Mohammad Mehdi; Ahmadi, Seyed Mohammad
ABSTRACT: Taking advantage of an adaptive Taylor series approximator, this research seeks to address a two‐loop robust controller for electrically‐driven differential drive wheeled mobile robots. A fictitious current signal is designed in the outer loop such that the good tracking performance as well as the asymptotic stability of system will be achieved. Also, the error of currents will be minimized by an actual control input in the inner loop. For both inner/outer loops, uncertain nonlinear functions can be approximated by adaptive Taylor series systems. To validate the proposed control algorithm, numerous simulations have been carried out with two different desired trajectories and multiple initial conditions. Also, the proposed controller is compared with a recent well‐designed robust adaptive fuzzy controller. In addition, to simplify the procedure of mathematical modelling of a wheeled mobile robot, the "Simscape Multibody" environment of "MATLAB" is used for 3D simulations.